Spectrophotometric Method for the Estimation of Mefloquine Hydrochloride - ARORA, VIMAL; BHANDARI, ANIL; KUMAR, BRIJESH; ARORA, RUBAL (Asian Journal of Chemistry, 2010)
A simple, specific, precise and accurate spectrophotometric method has been developed for the estimation of mefloquine hydrochloride in bulk and tablet dosage form. In the developed method aqueous methanol (10 % v/v) was used as the solvent. The absorption maximum of the drug was found to be 284 nm. The method was statistically validated according to International Conference on Harmonization Guidelines. Per cent mean recovery was obtained to be 99.1 %, whereas the coefficient of variance was found to be less than 2 %. The drug follows a linear Lambert-Beer law relationship with respect to the drug concentration in the range of 10-70 μg/mL, with linearity coefficient of 0.9991.